Narration and multimodality: The role of the human body and material objects in science teaching - Panagiotis Pantidos; George Kaliampos; Konstantinos Ravanis (Institute of Advanced Engineering and Science, 2022)
This article seeks to shed light on the semiotic approach to science teaching and learning. Essentially, the mental representations of learners are also affected by the sign vehicles employed to communicate ideas in the material world. Thus, any learning object also appears as a material representation, consisting of acoustic and visual forms, which affect its content. The human body’s kinetic modalities, spatial configurations (i.e., graphs, images), material objects, prosody, as well as the written and spoken word constitute the perceptual data that encode the concepts. This particular paper deals with the possibility that the more emphatic signifiers, i.e., the human body and material objects, can create narrative spaces and produce meaning during science teaching. It also discusses alternative uses of material objects along with the multiple interpretations their visual images can evoke. As regards the human body, iconic, deictic, and ergotic gestures are analyzed as forms that produce meaning and are autonomous and dynamic when working with the other semiotic systems. Both material objects and the human body rely upon the ability of the learners’ imagination to transport them to narrative worlds located outside the classroom.